Singular-Value Decomposition Based Kinematic Analysis of the Metamorphic Multifingered Hand - Cui, Lei; Dai, J. (ASME Press, 2010)
This paper investigates kinematics of the metamorphic multifingered robotic hand based on screw system analysis and singular value decomposition. The paper integrates the singular value decomposition with screw system and generates the reciprocity-based Jacobian matrices of a multifingered hand. This leads to the geometric constraint equation of the articulated palm as the typical feature of this robotic hand and to the kinematics characteristics equation of the hand. Symbolic singular values of the sub-matrices are derived and applied to obtaining analytical solution to inverse kinematics. The singular value decomposition helps identifying finger displacement and velocity with effect from the articulated palm and extra degrees of freedom are examined with the singular value analysis to avoid the singularities.